Efficacy of Four Different Feeds for Producing Hatchery Raised Red Claw Crayfish (Cherax quadricarinatus) - Kiriyakit, A.; Suwannagate, K. (International Journal of Agricultural Technology, 2018)
This research was initiated in order to determine effectiveness of locally available Thailand feeds and homemade (domestically manufactured) diets for best production of hatchery raised Red Claw Crayfish (Cherax quadricarinatus). A higher cost commercially manufactured shrimp feed was also examined. Brooding red claw crayfish were individually reared and fattened with four different feed treatments; earthworm segments, oyster meat, homemade mixed feed and commercial shrimp pellet feed. Feeding occured for 30 days, prior to transfer of all red claw crayfish to a pool mating tank. Gravid females for each feed treatment were collected and recorded at 15 day intervals, until day 45 of the breeding period. Total hatchery production for incubation times, number and size of free living juveniles, as well as survival and growth of 1 month old crayfish were determined, comparing performance of all brood crayfish. Results showed that brood crayfish fattened with oyster meat and homemade mixed feed, spawned faster and with higher fecundity, than brood crayfish fattened with earthworm segments and commercial shrimp pellet feed. Brood crayfish fattened with oyster meat spent longest incubation times. However, they gave similarly free living juvenile recruitment numbers to those brood fattened with homemade mixed feed and shrimp pellet feed. Even though the brood crayfish fed homemade mixed feed produced largest sized free living juveniles, juveniles fed with oyster meat showed better overall growth. Brood crayfish fattened with earthworm segments required shortest incubation times and produced highest numbers of free living juveniles. However, their free living juveniles were of the smallest size. Therefore, homemade feeds, or oyster meat feeds, are suggested to be the best choice for a maturation feed for red claw crayfish, for breeding. A better production performance, lower cost and simple preparation were observed factors.